Ginsenoside Rg3 Serves as an Adjuvant Chemotherapeutic Agent and VEGF Inhibitor in the Treatment of Non-Small Cell Lung Cancer: A Meta-Analysis and Systematic Review. (5th October 2016) - Xu, Tao; Jin, Zhichao; Yuan, Yuan; Wei, Huamin; Xu, Xinyao; He, Shulin; Chen, Shuntai; Hou, Wei; Guo, Qiujun; Hua, Baojin
Abstract : Objective. To evaluate ginsenoside Rg3 combined with chemotherapy for non-small-cell lung cancer (NSCLC) treatment, in a meta-analysis. Materials and Methods . We searched PubMed, EMBASE, the Cochrane Library, the China National Knowledge Infrastructure, and the VIP and Wanfang databases for eligible studies. We manually searched for printed journals and relevant textbooks. Statistical analyses were performed with Revman 5.3 and STATA 14.0 software packages. Results . Twenty studies were included. Ginsenoside Rg3 combined with chemotherapy could enhance response, improve disease control, prolong overall survival, improve patient quality of life, reduce leucocyte count decrease due to chemotherapy, reduce vascular endothelial growth factor expression in peripheral blood, and increase CD4/CD8 T cell ratio. Conclusion . Ginsenoside Rg3 combined with chemotherapy may enhance short-term efficacy and overall survival, alleviate treatment-induced side effects, reduce vascular endothelial growth factor expression, increase CD4/CD8 T cell ratio, and serve as a potential therapeutic regimen for NSCLC. However, considering the limitations, the conclusion should be interpreted carefully, and these results need to be confirmed by more high-quality trials.